Mathematical Approaches to Solving Difficult Problems in Chemistry - Khudoiberdievna, Abduvalieva Komila (Research Parks Publishing LLC, 2023)
The article presents simple ways to solve chemical problems using mathematical observation as part of a school chemistry course. Situations are also indicated, during which attention is drawn to the order of solving such problems, the sequence of their solution is noted, and examples of problems used in mathematical observations are given.